Contribuições para avaliação dos aspectos de conforto térmico em projeto de edificação residencial unifamiliar - Zankoski, Daniella Edina (2015)
The concept of architectural design today is closely linked to sustainable and bioclimatic architecture. Based on studies about housing and project analysis, bioclimatic strategies were used to obtain a comfortable ambience. The main objective of this work was to identify bioclimatic conditions for Pato Branco, a city in the state of Paraná, based on the climatic characterization of the site and the study of the guidelines set by the Brazilian standard of comfort NBR 15220-3 / 2003. According to this standard, Pato Branco is classified as Zone 2. Based on this information, the initial guidelines have been established for thermal comfort and energy efficiency, using software such as Analysis SUN-AIR to generate solar charts, analysis openings according to NBR 15220-3 / 2003 and cross ventilation using Fluxovento program.